Coastlines, structures and breakwaters proceedings of the international conference organized by the Institution of Civil Engineers and held in London, UK, on 19-20 March 1998 - Allsop, N. W. H. 1951- (Thomas Telford, 1998)
This work is a collection of papers from the 1998 Coastlines Structures, and Breakwaters conference and draws together a diverse sampling of extensive and recent advances that EU countries have made in the design, study and construction of significant breakwater structures.